Aerobic soil bacteria adapt to hypoxia by hybridizing fermentation with carbon storage - David L. Gillett; Thilini Koralegedara; Tess F. Hutchinson; Thanh Nguyen-Dinh; Thomas D. Watts; Jessica Solari; Manasi Mudaliyar; William J. Jowsey; Nadeesha Athukorala; Wei Wen Wong; Jake U. S. Locop; Ning Hall; et al. (Proceedings of the National Academy of Sciences, 2026)
In soil ecosystems, aerobic bacteria survive oxygen deprivation (hypoxia) by entering nonreplicative persistent states. In contrast to the well-studied metabolism of obligate and facultative anaerobes, little is known about how obligately aerobic bacteria adapt their metabolism to stay viable during hypoxia. The model obligate aerobe Mycobacterium smegmatis maintains redox homeostasis during hypoxia by mediating fermentative hydrogen production. However, the fate of organic carbon during fermentation is unresolved. Here we systematically profiled the metabolism of M. smegmatis during aerobic growth, hypoxic persistence, and the transition between these states. By integrating a differentially 13 C-labeled glucose isotopologue assay with paired metabolomics and proteomics, we observed M. smegmatis rerouted central carbon metabolism through the pentose phosphate pathway and/or Entner–Doudoroff pathways during hypoxia, while excreting high levels of hydrogen and acetate. Lipid and cryoelectron tomography analyses suggest M. smegmatis also stores carbon as glycerides in lipid droplets during hypoxia, which serve as a major reductant sink. Gene knockouts and knockdowns revealed that, while M. smegmatis depends on its hydrogen-producing hydrogenase for hypoxic survival, it can compensate for the disruption of acetate production and glyceride synthesis by producing and excreting other organic acids. We confirmed through an extensive genomic survey and biogeochemical measurements that diverse aerobic soil bacteria can store organic carbon and mediate fermentation during hypoxia. Altogether, this hybrid fermentative metabolism likely provides a competitive advantage in soils and other resource-variable environments by enabling bacteria, such as M. smegmatis , to simultaneously dispose excess reductant and maintain carbon stores during hypoxia.